Influence of performance in Spanish language and literature on physical education and music grades - Clares-Clares, Esperanza; Gómez-Mármol, Alberto (Frontiers in Education, 2022)
The aim of this research was to analyze the influence of performance in the subject of Spanish language and literature on the grades in the subjects of Physical Education and Music and whether there were differences by sex or not. The participating sample was made up by a total of 451 students (235 boys and 216 girls), aged between 10 and 13 years old, in the fifth and sixth grades of Primary Education. The results show, on the one hand, a positive correlation between the grades of the three subjects and, on the other hand, in terms of gender, significant differences only in the subject of Music whose grades are higher in girls compared to boys. Nevertheless, these statements should be considered taking into account that academic performance was measured only with one instrument ant that the sample, besides being limited in size, was accessed with a non-probabilistic method. Based on these results, it is suggested that future studies could encompass different research methodologies and include, in turn, new variables as well as other collectives which are also concerned with this regard.